Synthesis and Characterization of Nano Chitosan from Vannamei Shrimp Shell (Litopenaeus vannamei) - Dian Wijaya Kurniawidi; Siti Alaa; Eva Nurhaliza; Desti Olga Safitri; Susi Rahayu; Muhamad Ali; Muhamad Amin (Jurnal Ilmiah Perikanan dan Kelautan, 2022)
Highlight Research New method to synthesis nano chitosan from Vannamei shrimp with high Deacetylation Degree Nano chitosan from Vannamei shrimp can adsorb heavy metal Fe up to 81.35% Shrimp shells as an alternative adsorbents for Fe   Abstract Shrimp cultivation produces shrimp wastes in several forms, including shells from the molting process. Shrimp shell waste can be used as a source of nano chitosan. Many researches have used nano chitosan for various applications, one of which is to adsorb heavy metal pollution. This present study aimed to extract chitosan from shrimp shells and investigate the ability of nano chitosan to adsorb Fe metal. The research began by isolating chitin and chitosan from shrimp shells through deproteinization, demineralization, and deacetylation. The obtained chitosan was afterward characterized using Fourier Transform Infrared (FTIR). Furthermore, the glassy ionic method was used to synthesize nano chitosan. Nano chitosan was characterized using a scanning electron microscope (SEM), and the Fe metal adsorption ability was measured using Atomic Absorption Spectroscopy (AAS). The FTIR results showed that the synthesized shrimp shells had successfully formed chitin compounds with the appearance of the C-O-C functional group, while the chitosan compounds with the appearance of O-H and N-H groups. The SEM characterization showed that nano chitosan with a size of 173.71 nm was successfully formed with identical morphology in the form of a flat (spherical), elongated, and irregular position. The nano chitosan was able to absorb Fe solution up to 81.35%. Therefore, nano chitosan from the shrimp shells is suitable as an adsorbent of heavy metal Fe.